Odpowiedź :
Cześć!
a)
[tex]4x-7=2x+9\\\\4x-2x=9+7\\\\2x=16 \ \ /:2\\\\\huge\boxed{x=8}[/tex]
b)
[tex]3-8x=18-3x\\\\-8x+3x=18-3\\\\-5x=15 \ \ /:(-5)\\\\\huge\boxed{x=-3}[/tex]
c)
[tex]2-x=12+7x\\\\-x-7x=12-2\\\\-8x=10 \ \ /:(-8)\\\\\huge\boxed{x=-1,25}[/tex]
d)
[tex]3x+5x-6=6x+2\\\\3x+5x-6x=2+6\\\\2x=8 \ \ /:2\\\\\huge\boxed{x=4}[/tex]
e)
[tex]5-9x+6=2x+14-x\\\\-9x+11=x+14\\\\-9x-x=14-11\\\\-10x=3 \ \ /:(-10)\\\\\huge\boxed{x=-0,3}[/tex]
Odpowiedź:
a) 4x-7= 2x+9
4x-2x= 9+7
2x= 16 /:2
x=8
spr... 4*8 -7= 2*8+9
32-7= 16+9
25=25
L=P
b) 3-8x =18-3x
-8x +3x= 18 -3
-5x= 15 /:5
x= -3
spr... 3-8* (-3) = 18 -3*(-3)
3+24= 18 +9
27= 27
L=P
c) 2-x= 12 +7x
-x -7x= 12 -2
-8x= 10 /:8
x= - 10/8= - 1 i 2/8= - 1 i 1/4
spr.. 2- (-1 i 1/4) = 12 + 7* (- 1 i 1/4)
3 i 1/4= 12 + 7(- 5/4)
3 i 1/4 = 12- 8 i 3/4
3 i 1/4= 3 i 1/4
L=P
d) 3x+5x -6= 6x+2
3x+5x -6x= 2 +6
2x= 8 /:2
x=4
spr... 3*4 +5*4 -6= 6*4 +2
12 +20 -6= 24+2
26=26
L=P
e) 5-9x +6= 2x+14-x
-9x -2x+x= 14 -6- 5
-10x= 3 /:10
x= - 3/10
spr... 5- 9*(-3/10) +6= 2*(-3/10) +14- (-3/10)
5 + 27/10 +6= -6/10 +14 +3/10
5+ 2 i 7/10 +6= 13 i 7/10
13 i 7/10= 13 i 7/10
L=P
Szczegółowe wyjaśnienie: